Sida brachyclada (Malveae, Malvoideae, Malvaceae): a new threatened species from the semiarid mountains of Bahia, Brazil - Guerra, Gabriel C.; Colli-Silva, Matheus; Bovini, Massimo G.; Giulietti-Harley, Ana Maria (Phytotaxa, 2025)
Sida brachyclada is a newly described shrubby species of Sida sect. Cordifoliae (Malvaceae, Malvoideae), endemic to the semiarid mountains of Bahia. It occurs in ecotonal zones of cerrados, caatingas, and submontane forests, at elevations ranging from 300 to 1169 m. The species is distinguished by a unique combination of morphological traits: short lateral brachyblasts with prominent scars from deciduous leaves and stipules, small ovate-elliptic leaves, and terminal, lax inflorescences bearing long-pedicellate flowers. A preliminary conservation assessment following IUCN criteria classifies the species as Endangered (EN). Supporting materials include an illustration, photographs, a diagnostic plate based on the Lankester Composite Dissection Plate, a distribution map, and a key for Bahian species from Sida sect. Cordifoliae.